2017
DOI: 10.1136/thoraxjnl-2016-209376
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic deprivation and the outcome of pulmonary rehabilitation in England and Wales

Abstract: BackgroundPulmonary rehabilitation (PR) improves exercise capacity and health status in patients with COPD, but many patients assessed for PR do not complete therapy. It is unknown whether socioeconomic deprivation associates with rates of completion of PR or the magnitude of clinical benefits bequeathed by PR.MethodsPR services across England and Wales enrolled patients to the National PR audit in 2015. Deprivation was assessed using Index of Multiple Deprivation (IMD) derived from postcodes. Study outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 24 publications
3
52
2
1
Order By: Relevance
“…Epidemiological studies suggest that only a proportion of eligible patients receive and/or complete pulmonary rehabilitation; less than 50% of those referred in a recent snapshot audit of PR services in England and Wales. 133 Physically frail patients are less likely to complete PR. 134 The breathlessness services described above, and/or less intensive exercise modalities e.g.…”
Section: Integration Of Palliative Care In Copd Servicesmentioning
confidence: 99%
“…Epidemiological studies suggest that only a proportion of eligible patients receive and/or complete pulmonary rehabilitation; less than 50% of those referred in a recent snapshot audit of PR services in England and Wales. 133 Physically frail patients are less likely to complete PR. 134 The breathlessness services described above, and/or less intensive exercise modalities e.g.…”
Section: Integration Of Palliative Care In Copd Servicesmentioning
confidence: 99%
“…Furthermore, a cohort study from the UK showed an association between socioeconomic disadvantage and lower adherence to and completion of PR 15. Socioeconomic disadvantage was not, however, associated with lower gains in exercise performance or health status following PR 15.…”
Section: Pulmonary Rehabilitation and Exercise Trainingmentioning
confidence: 97%
“…Furthermore, a cohort study from the UK showed an association between socioeconomic disadvantage and lower adherence to and completion of PR 15. Socioeconomic disadvantage was not, however, associated with lower gains in exercise performance or health status following PR 15. Notably, individuals with COPD who have a spouse or partner caregiver have an 11-fold greater odds of participation in PR than those lacking this social support 16.…”
Section: Pulmonary Rehabilitation and Exercise Trainingmentioning
confidence: 99%
“…The value of such population-level approaches is evident in the paper by Steiner and colleagues5 published in Thorax . Using data from the 2015 National COPD Clinical Audit Programme (England and Wales), Steiner and colleagues present an analysis of uptake and performance of participants across 230 pulmonary rehabilitation services,6 including over 7000 participants with COPD 7.…”
mentioning
confidence: 99%
“…Given that COPD is disproportionally represented in lower socioeconomic groups, worldwide8 examination of the influence of social factors on implementation of pulmonary rehabilitation has been lacking to date. Recommendations of Steiner and colleagues include ‘raising awareness of the benefits of pulmonary rehabilitation to patients from deprived areas and changing referral practice among healthcare workers who provide care in these areas’ 5. The latter may be facilitated by clear processes including a referral pathway from hospital care and financially incentivised support for making pulmonary rehabilitation a usual part of primary care for people with COPD in these areas 12…”
mentioning
confidence: 99%